Estudo papeleiro da mistura dos "rolos-restos" das fábricas de compensados do Estado do Amazonas - Corrêa, Antônio de Azevedo (Acta Amazonica, 1982)
This study involves the use of leftover wood rolls from the manufacture of plywood in Amazonas State for use in the pulp and paper industry. This is a continuation of a previous study with the same goal, but focussing on individual logs. The material utilized in this research was a mixture of chips of rolls, corresponding to the following species: Copaifera multijuga Hayne, Hevea guianensis Aubl., Jacareúba Calophyllum brasiliense Camb., and Virola Virola surinamensis Warb., chosen because of their chemical composition; each species having the same percentage by weight, in the pulp mixture. The methods used in the samples were those traditionally utilized to evaluate raw materials for the pulp and paper industry. Results obtained are discussed is in relation to chemical analysis, classification, micromeasurements of fiber density of chips, and cooking. The sulphur-soda process and soda and sulphate process for the production of chemical pulp and neutral sulphite are compared. Bleaching of raw pulp, affected by C.E.H.H., C.E.D.E.D. and C.E.H.D.E.D. processes is examined, as well as are the physical-mechanical characteristics of the paper and corrugated board obtained from the raw and bleached pulp. Numerous conclusions are inferred, the most important of which is that pulp produced from residual logs from plywood manufacturing is of practical use, especially in the production of corrugated board.